An implantable antenna designed for ease of manufacturing. Issue 3 (March 2016) - Rodriguez, Miguel; Furse, Cynthia M.
ABSTRACT: This article describes an improved method of manufacturing PIFA antennas for medical implants, and associated design considerations. The antenna is manufactured "upside down, " by molding the silicone superstrate first, placing the radiating element against it, and then pouring epoxy into the mold to form the substrate. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:619–623, 2016